Peranan Pemerintah Daerah Dalam Meningkatkan Kinerja Corporate Social Responsibility (CSR) Di PT. Nusa Halmahera Minerals - GUMURU, DENIS (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRAK In this research writer to use descriptive research with quantitative approach. The method of researching is, manner to gather data with to use technic datacollecting and data collecting instrument. In this relation, sometimes are based on the criteria or certain consideration and this research dating using primet data in cuesioner form. In accordance with position, tash and function mining and energy department is an element region of government implementer. The hook with development policy CSRÂ  program in this research, variable to search connet with relevan components. With actions mining and energy department to include direction technic target and stategy from all leinds of step to a chieve certain target. Region government part and public participation very influential to occupation corporate social responsibility/CSR PT. Nusa Halmahera Minerals. Region government part in this case mining and energy department effarting to increase occupation corporate social responsibility/CSR in pass particular programs performed more it development, the meaning is CSR program has given the big contribution for government and mine cirele public and that awn company. Keyword : The role of region government, corporate social responsibility